Radiographic assessment of AO 44-B1 and -B2 ankle fractures - Labronici, Pedro; Fogagnolo, Fabricio; Belangero, William; Amorim, Luiz (Journal of the Foot & Ankle, 2021)
Objective: To verify if there is a type of image that guides the surgeon in recommending surgical treatment for ankle fractures and assess whether this decision is associated with the evaluator’s age and experience, considering surgeons of different nationalities. Methods: We analyzed 3 different presentations of radiographic images of ankle fractures in 36 patients: anteroposterior and lateral views, true anteroposterior and lateral views, as well as the 3 grouped images. Images were assessed randomly and independently by 89 professionals of different nationalities, ages, and experience. Results: Among professionals from Ecuador, Argentina, Mexico, and Chile, surgery recommendations were more frequent when images were presented in true anteroposterior and lateral views. For professionals from Peru, Venezuela, Bolivia, Paraguay, Brazil, Colombia, Uruguay, and Guatemala, as well as globally, recommendations for surgery were more frequent when grouped images of the 3 positions were presented. In all countries and globally, we verified lower frequencies of surgery recommendations when presenting only anteroposterior and lateral views. Conclusion: In most countries, surgery recommendations were more frequent when grouped images of all 3 views were presented. On the other hand, the highest frequencies of surgery recommendations were observed when images were presented only in true anteroposterior and lateral views. Surgery recommendations were not associated with the experience (years since graduation) of the evaluating physician. Level of Evidence IV; Prognostic Studies; Case Series.